Public Relations Strategy Analysis Crisis Communications - Liyana Ansharah Zimal; Attaf Awamiri Aysar (Journal La Sociale, 2021)
Crisis communication is the exchange of information between an organization and its constituents during and after the occurrence of a crisis. This research employs a descriptive technique and a qualitative method. Techniques for data gathering include observation, interviewing, and documenting. The aim of this research is to conduct an empirical examination of the execution of strategies and supporting and inhibiting variables in crisis communication in public relations. The findings of this research suggest that a crisis communication plan should be suitable and swift in order to overcome public reaction and avoid a protracted crisis communication. Communication in Times of Crisis Pre-Crisis management is carried out by Public Relations, namely in the preparation (Planning) stage, which includes the establishment of a Public Relations team responsible for providing information, a clean-up and executive summery formation team, and Crisis-Response, namely the manufacturing stage. Press releases, clarifications, establishing stakeholder and media relations, and finally, Post-Crisis, namely the advancement of Public Relations not only to improve the company's image but also to improve performance, press conferences, and dissemination of publications are also implemented to improve things in the short and long term through programs